INVESTIGATING THE CLIMATE CHANGE TREND AND THE URBAN HEAT ISLAND OF TEHRAN DISTRICT 1 USING THE REMOTE SENSING TECHNOLOGY AND GIS - Nikoo Razavi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The rise in the earth's temperature and the formation of heat islands in metropolitan areas have turned into one of the environmental challenges resulting from the unplanned growth of these cities. These urban issues more than ever affect metropolitan areas of Iran, such as Tehran. Environmental shortages and the resulting pollution are specific instances of such problems. Global warming and the formation of heat islands in the 22 districts of Tehran are other examples of these problems that have led to recent environmental issues. Satellite images are increasingly used in urban environmental studies as they provide an integrated view and reduce the time and costs of studies. This study aims to investigate the reasons for temperature variations and the formation of a heat island in District one of Tehran following the development of this area during the past decades. Landsat TM, ETM, and OLI imagery of the years 1984 to 2020, thermal remote sensing techniques, and the GIS are used to analyze the data, and the correlation between the data was obtained via the SPSS software. The results revealed that the earth's surface temperature in district one of Tehran has increased during the past thirty-eight years. During this period, the land use in Tehran district one has changed considerably. The urban land use has increased from 16 percent in 1984 to 35 percent in 2020, and the vegetation has decreased from 32 percent to 14 percent. Considering these findings, it is clear that the trend of temperature rise in district one of Tehran has become an environmental issue, and land-use variations such as reduced vegetation and accelerated urbanization are the factors affecting this issue.